Analisis Perbandingan Harga Saham dan Volume Perdagangan Saham Sebelum dan Sesudah Stock Split - Indarti, Iin; Purba, Desti Mulyani Br. (Jurnal Ilmiah Aset, 2011)
Stock split is one kind of corporate action implemented by companies in order to rearrange stock price to be at a more liquid range and provide more positive signal to investor. The stock split carried out on the basis of two theories. According to the Trading Range Theory, the high stock price is the driving force for the company to split its stock with the hope of increasing the liquidity of stock trading, putting the stockon the optimal trading range and will be more and more investors that will be investing. Signaling Theory states that the stock split is the conveyance of information about performance and prospects to the market. The purpose of this research was to analyze the differences of stock price and stock trading volume activity pre and post stock split event, so that investors could use this event to gain benefit. This research used event study method to observe average stock price, and trading volume activity within five days pre and post event date. This research used secondary data collected from Indonesian Capital Market Directory ( ICMD) 2007. The data used in research was taken from : 10 days announcement date of stock split applied as event date (to), daily closing price, the amount of daily traded share and the amount of listed share. There were 9 companies which implemented stock split policy 2007. Results of the study showed that there were significant differences of stock price and trading volume activity from pre and post event.